en - Al Qusyoi Ar, M. Haddad; Dara Damanik, Emiliya Sukma; Asty, Rafadila; Miha Sy, T Zunita (e-Journal of Linguistics; Vol 17 No 1 (2023): en, 2022)
This study aims to analyze the word formation that researchers have found in the lyrics of Justin Bieber's song entitled Baby. The method used by the researcher is a qualitative research method, where the researcher investigates the formation of words in the lyrics of Justin Bieber's song entitled Baby. The data is taken from data sources, namely from Justin Bieber song lyrics in the browser. The results of this study are the researchers found five types of forming of words, namely three words from clipping, six words from compounding, one word from blending, one word from coinage, and one word from inflection in the lyric of Justin Bieber’s song entitled Baby.